Peran Sistem Informasi Manajemen Pendidikan Dalam Meningkatkan Mutu Pendidikan: Studi Kasus di SDIT Aziziyyah - Desi Sawitri; Nuraini; Ahmad Ansori; Reka Adriyan Saputra (IAIN Parepare, 2025)
This study analyzes the role of the Education Management Information System (Education MIS) in improving educational quality at SDIT Aziziyyah, Pekanbaru. The research addresses the empirical gap regarding integrated implementation of Education MIS in Islamic primary schools, particularly in supporting operational efficiency, instructional monitoring, and data-driven decision making. A descriptive qualitative case study was conducted, collecting data through interviews, observation, and documentation, and validated through source triangulation. Findings indicate that Education MIS significantly improves administrative efficiency, real-time student achievement monitoring, transparency for parents, and data-based managerial decision-making. This study extends previous research by showing that Education MIS also supports pedagogical practices, learning evaluation, and school-parent collaboration. The study highlights that integrated Education MIS is a strategic tool for transforming management in Islamic primary schools, with cloud-based development recommended for system sustainability